2011
DOI: 10.1111/j.1435-5957.2010.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Homeless networks and geographic concentration: Evidence from Osaka City

Abstract: Homeless people in Osaka City are geographically concentrated. The purpose of this paper is to empirically test the hypothesis that the geographic concentration arises from the benefits of homeless networks. A spatial regression model is estimated using data on Osaka City's homeless population by census blocks. The positive coefficient of the spatially lagged dependent variable enables us to explore how a homeless network across census blocks, outweighs a negative competition effect. The estimated results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Previous research has found that housed people with mental illnesses migrate to locations where they have received care, 11 and that those with serious mental illnesses change their location more frequently than either people with serious physical illnesses or people without a medical condition. 12 Migration has also been shown to be a factor contributing to concentrations of homeless individuals in multiple urban centres including Sao Paolo, 13 Osaka, 14 Philadelphia and New York. 15 Importantly, few if any studies have examined geographic migration or service use patterns preceding the spatial concentration of people who are both homeless and mentally ill.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that housed people with mental illnesses migrate to locations where they have received care, 11 and that those with serious mental illnesses change their location more frequently than either people with serious physical illnesses or people without a medical condition. 12 Migration has also been shown to be a factor contributing to concentrations of homeless individuals in multiple urban centres including Sao Paolo, 13 Osaka, 14 Philadelphia and New York. 15 Importantly, few if any studies have examined geographic migration or service use patterns preceding the spatial concentration of people who are both homeless and mentally ill.…”
Section: Introductionmentioning
confidence: 99%
“…Motivations to travel were found to be similar to domiciled citizens and related to work, medical services, eating and social activities (May, 2003;Wolch et al, 1993). Travel for some was influenced by respondents' social networks (Iwata & Karato, 2011), though only three persons' mobility was greatly influenced by family.…”
Section: Discussionmentioning
confidence: 91%
“…We also know that the homeless are forced into public spaces more frequently than domiciled persons, and that this influences homeless mobility in several ways, even without considering transportation disadvantage experienced by the poor (Hine & Mitchell, 2001). Homeless mobility is affected by urban planning (Braverman, 2010), legislation (Doherty et al, 2008;May, 2003;Mitchel, 1997), other factors such as physical disability, need of restrooms and special services (Iwata & Karato, 2011;Rahimian, Wolch & Koegel, 1992), and by criminal justice response (Kaufman, 2021;Wardhaugh, 1996). Persons living in SROs and shelters are also noted as sometimes having affected mobility as a direct result of their housing situation (Nair, 2016;Rankin, 2015;Rollinson, 1990).…”
Section: Introductionmentioning
confidence: 99%